EFEKTIVITAS DOSIS KARBON TETRAKLORIDA (CCl4) TERHADAP TIKUS (Rattus norvegicus L.) SEBAGAI HEWAN MODEL FIBROSIS HATI - Fahri Fahrudin; Sri Ningsih; Hajar Indra Wardhana; Dinda Rama Haribowo; Fathin Hamida (Research Center for Biology-Indonesian Institute of Sciences, 2020)
Liver damage can produce fibrosis condition both acute and chronic. Development of liver fibrosis in animal models is valuable information in order to gain new entities for treatment. The aim of this study is to get an optimal condition of CCl4 induction for achieving animal models of liver fibrosis. CCl4 diluted in coconut oil was administrated orally for 6 consecutive weeks. Total 25 male rats were divided into 5 treatment groups, namely, P1 was a normal group (without CCl4). P2 (CCl4 40%), 1 ml/kg bw 3 times a week. P3 (CCl4 40%), 0.5 ml/kg bw 3 times a week, P4 (CCl4 10%) 1 ml/kg bw 3 times a week, and P5 (CCl4 10%) 1 ml/kg bw twice a week. The analyzed parameters were the activity of liver enzymes, macro and microscopic liver damage, and the percentage of rat deaths. The results of this study indicated an increase in liver enzymes in all treatments which was higher than P1 (P<0.05). Analysis of liver histopathology exhibeted the same result. However, if viewed the percentage of rat deaths, P5 demonstrated the lowest compared to all treatment groups. It could be concluded that the administration of CCl4 (10%) was able to create an animal model of liver fibrosis optimally.